2022
DOI: 10.1021/acs.analchem.2c02337
|View full text |Cite
|
Sign up to set email alerts
|

Integrated System for On-Site Rapid and Safe Screening of COVID-19

Abstract: Since the outbreak of coronavirus disease 2019 (COVID-19), the epidemic has been spreading around the world for more than 2 years. Rapid, safe, and on-site detection methods of COVID-19 are in urgent demand for the control of the epidemic. Here, we established an integrated system, which incorporates a machine-learning-based Fourier transform infrared spectroscopy technique for rapid COVID-19 screening and air-plasma-based disinfection modules to prevent potential secondary infections. A partial least-squares … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1

Citation Types

0
1
0

Year Published

2023
2023
2024
2024

Publication Types

Select...
2
1

Relationship

0
3

Authors

Journals

citations
Cited by 3 publications
(1 citation statement)
references
References 57 publications
0
1
0
Order By: Relevance
“…A partial least squares discrimination analysis and a convolutional neural network model were built using the collected infrared spectral dataset of serum samples. The sensitivity, specificity and accuracy all reach over 94% from the blind test samples [46] . Zhang et al reported a rapid and sensitive magneto fluidic immune-PCR platform that can address the current gap in POC serological testing for COVID-19.…”
Section: Related Workmentioning
confidence: 89%
“…A partial least squares discrimination analysis and a convolutional neural network model were built using the collected infrared spectral dataset of serum samples. The sensitivity, specificity and accuracy all reach over 94% from the blind test samples [46] . Zhang et al reported a rapid and sensitive magneto fluidic immune-PCR platform that can address the current gap in POC serological testing for COVID-19.…”
Section: Related Workmentioning
confidence: 89%